GATA zinc finger domain‐containing protein 2A (GATAD2A) deficiency reactivates fetal haemoglobin in patients with β‐thalassaemia through impaired formation of methyl‐binding domain protein 2 (MBD2)‐containing nucleosome remodelling and deacetylation (NuRD) complex. (17th May 2021) - Liang, Yunhao; Zhang, Xinhua; Liu, Yongqiong; Wang, Liren; Ye, Yuhua; Tan, Xuemei; Pu, Jiajie; Zhang, Qianqian; Bao, Xiuqin; Wei, Xiaofeng; Li, Dongzhi; Kurita, Ryo; et al.
Summary: Reactivation of fetal haemoglobin (HbF) expression is an effective way to treat β‐thalassaemia and sickle cell anaemia. In the present study, we identified a novel GATA zinc finger domain‐containing protein 2A ( GATAD2A ) mutation, which contributed to the elevation of HbF and ameliorated clinical severity in a patient with β‐thalassaemia, by targeted next‐generation sequencing. Knockout of GATAD2A led to a significant induction of HbF in both human umbilical cord blood‐derived erythroid progenitor‐2 (HUDEP‐2) and human cluster of differentiation (CD)34 + cells with a detectable impact on erythroid differentiation. Furthermore, heterozygous knockout of GATAD2A impaired recruitment of chromodomain helicase DNA‐binding protein 4 (CHD4) to the methyl‐binding domain protein 2 (MBD2)‐containing nucleosome remodelling and deacetylation (NuRD) complex. Our present data suggest that mutations causing the haploinsufficiency of GATAD2A might contribute to amelioration of clinical severity in patients with β‐thalassaemia.